IRAK3 is upregulated in rheumatoid arthritis synovium and delays the onset of experimental arthritis - Federica Borghese; Richard O. Williams; Felix I. L. Clanchy; Felix I. L. Clanchy (Frontiers in Immunology)
Tumour necrosis factor (TNF) is a potent inducer of endotoxin tolerance-associated molecules, such as interleukin-1 receptor-associated kinase 3 (IRAK3), and also a therapeutic target in inflammatory autoimmune diseases, as it upregulates the production of inflammatory mediators. The role of IRAK3 was assessed in rheumatoid arthritis (RA), a disease which is amenable to TNF blockade. As a variant of IRAK3 lacks the death domain required for its canonical role, isoform expression was determined in different inflammatory milieu by immunoblotting. RA synovial explant expression of IRAK3 was measured by qPCR. The expression of the larger, “classical” IRAK3 isoform predominated in macrophages treated with various stimuli. The expression of IRAK3 was higher in RA synovium compared to osteoarthritis synovium. Using collagen-induced arthritis, a murine model of RA, the immunomodulatory role of IRAK3 was investigated with wild-type (WT) and IRAK3-deficient mice expressing the MHC-II Aq allele. Disease progression was significantly accelerated in IRAK3−/− mice. In addition, the circulating levels of IL-1β were greater, and there were fewer Tregs both before and after the onset of disease. Inflammatory gene expression was higher in the arthritic paws of IRAK3−/− mice. This study demonstrates that IRAK3 deficiency accelerates the progression of arthritis and increases molecular markers of disease severity.”